Leading Within Boundaries: Leadership Practices for Enhancing Teacher Well-Being in Pesantren-Based Schools - Akmal Mundiri; Hasan Baharun; Najiburrohman; Rahimah Embong (Faculty of Educational Sciences, UIN (State Islamic University) Syarif Hidayatullah Jakarta, 2025)
Abstract Teachers in pesantren (Islamic boarding schools) often work at the intersection of institutional obligations, religious devotion, and personal life, making their psychological well-being vulnerable to emotional strain and blurred work-life boundaries. Although educational leadership research has examined formal management and organizational support, little is known about how everyday leadership practices protect teachers' psychological well-being in pesantren-based schools. This study investigates how leadership behaviors preserve and enhance teacher well-being in two Indonesian Islamic boarding schools. Using a qualitative multiple-case study design, data were collected from 18 participants, including principals, teachers, and administrative staff, through semi-structured interviews, participant observation, and document analysis between January and April 2025. The data were analyzed using inductive thematic analysis and cross-case comparison. The findings identify three mutually reinforcing leadership dimensions: relational leadership through exemplary conduct, collegiality, and caring interactions; spiritual leadership through the reinforcement of religious and professional meaning; and managerial leadership through empowerment, recognition, workload regulation, and collective responsibility. The study proposes boundary-setting leadership as an integrated model that combines relational, spiritual, and managerial practices to sustain teachers' psychological well-being in pesantren-based schools. This model contributes to debates on educational leadership in faith-based institutions by showing how leaders negotiate institutional commitment and teachers' need for psychological sustainability. Abstrak Guru di pesantren sering bekerja pada persinggungan antara kewajiban institusional, pengabdian keagamaan, dan kehidupan pribadi, sehingga kesejahteraan psikologis mereka rentan terhadap tekanan emosional dan kaburnya batas antara pekerjaan dan kehidupan pribadi. Meskipun penelitian tentang kepemimpinan pendidikan telah banyak membahas manajemen formal dan dukungan organisasi, masih sedikit kajian yang menjelaskan bagaimana praktik kepemimpinan sehari-hari melindungi kesejahteraan psikologis guru di sekolah berbasis pesantren. Penelitian ini mengkaji bagaimana perilaku kepemimpinan mempertahankan dan meningkatkan kesejahteraan guru di dua pesantren di Indonesia. Dengan menggunakan desain studi kasus ganda kualitatif, data dikumpulkan dari 18 partisipan, yang terdiri atas pimpinan sekolah, guru, dan staf administrasi, melalui wawancara semi-terstruktur, observasi partisipatif, dan analisis dokumen pada periode Januari hingga April 2025. Data dianalisis menggunakan analisis tematik induktif dan perbandingan lintas kasus. Temuan penelitian mengidentifikasi tiga dimensi kepemimpinan yang saling menguatkan, yaitu kepemimpinan relasional melalui keteladanan, kolegialitas, dan interaksi yang penuh kepedulian; kepemimpinan spiritual melalui penguatan makna religius dan profesional; serta kepemimpinan manajerial melalui pemberdayaan, pengakuan, pengaturan beban kerja, dan tanggung jawab kolektif. Penelitian ini mengusulkan kepemimpinan penetapan batas kerja sebagai model terpadu yang menggabungkan praktik relasional, spiritual, dan manajerial untuk menopang kesejahteraan psikologis guru di sekolah berbasis pesantren. Model ini berkontribusi pada diskursus kepemimpinan pendidikan di lembaga berbasis keagamaan dengan menunjukkan bagaimana para pemimpin menegosiasikan komitmen institusional dan kebutuhan guru akan keberlanjutan psikologis.